Conducting remote medical asylum evaluations in the United States during COVID-19: Clinicians' perspectives on acceptability, challenges and opportunities. (November 2021) - Pogue, Megan; Raker, Elsa; Hampton, Kathryn; Saint Laurent, May-Lorie; Mishori, Ranit
Abstract: Background: Due to the COVID-19 pandemic, medical evaluations for asylum are being performed predominantly remotely. We sought to describe these evaluations and identify barriers. Methodology: This study utilized an online survey to assess clinician perspectives and experiences regarding remote asylum evaluations. Results: Clinicians reported positive experiences regarding remote interpretation (85%, 51/60), history taking (82.4%, 61/74), rapport building (81.3%, 61/75), and conducting the psychiatric exam (65.7%, 44/67). Concerns were more frequently reported with performing remote physical examinations (83.3%, 15/18). Although the majority denied challenges with technology (62.5%, 45/72), internet (60.8%, 45/74) or clients having difficulty acquiring technology (58.6%, 41/70) or finding private spaces (54.2%, 39/72), these aspects did represent barriers. Discussion: Remote evaluations were relatively easy to perform and acceptable to clinicians. This may facilitate easier access for asylum seekers beyond the pandemic. Highlights: The COVID-19 pandemic forced clinicians to conduct forensic asylum evaluations in the US remotely. This survey assessed US-based clinicians' experience with the provision of forensic asylum evaluations remotely. Clinicians largely denied difficulties with translation, rapport, or history taking. Most clinicians denied having problems with internet or technology. Remote physical examinations were more challenging in comparison to mental health evaluations. Overall, remote evaluations were "time savers" and easier than expected.